Adsorption of copper ions from environmental water samples by graphene 0xide/cellulose acetate- mixed matrix membrane - Kamaruzaman, Sazlinda; Mohammad Nasir, Nur Najihah; Johari, Ili Syazana; Yahaya, Noorfatimah; Loh, Saw Hong (Malaysian Institute of Chemistry, 2023)
Nowadays, the removal process of heavy metal ions by utilizing membrane technology, such as mixed matrix membrane (MMM), has many advantages, such as high effectiveness in adsorption performance and cost, rapid and simple procedures. In this study, a composite mixed matrix membrane, namely graphene oxide-cellulose acetate (GO/CAM-MMM) is developed. Cellulose acetate (CA) is a biodegradable polymer, and graphene oxide (GO) has high abundancy with oxygen-containing functional groups and has been widely utilized as an adsorbent. The GO/CAM-MMM has been characterized using Fourier transform Infrared (FTIR) spectroscopy and field emission scanning electron microscopy (FESEM) and used as an adsorbent to remove Cu2+ ions in water samples. A maximum adsorption capacity of 143 mg/g at 30 min of contact time for the removal of 50 ppm of Cu2+ ion at pH 5 of water samples was achieved by the best performing MMM, which was fitted with a Langmuir isotherm and a pseudo-second-order kinetic study. Thus, the developed membrane has good potential for Cu2+ ions removal from aqueous solution and can be utilized for real waste water treatment due to its simple preparation, low cost and time.